Resignify the body: the education of the senses (Research, Society and Development, 2019)
This essay reflects on the understanding of body in Merleau-Ponty and the contributions of his phenomenology to Physical Education, considering the education of the senses in a pedagogical perspective. Therefore, this study is based on bibliographical research and the qualitative approach. From the Merleau-Pontyan concepts, we present the idea that the body is not a passive instrument before the world, but is based on time and space, which carries an intentionality, being at the same time the subject and object of perception. We conclude that a sensitivity-oriented learning, through a pedagogical action delineated by an experience of corporeity, makes it possible to re-signify the rationalized body and thus create new meanings in the teaching-learning process.